Using experimental methods and CSD data for investigating the products of the reaction between 2-((2-aminoethyl)amino)ethanol with CdI2 and CdI2/HgI2-mixtures. Issue 7 (3rd April 2017) - Hakimi, Mohammad; Mardani, Zahra; Moeini, Keyvan; Feizi, Nourollah; Mohr, Fabian
Abstract: The binding modes of 2-((2-aminoethyl)amino)ethanol-based ligands were explored using the Cambridge Structural Database (CSD). To extend this field, a new cadmium complex containing 2-((2-aminoethyl)amino)ethanol (AEAE), [Cd(AEAE)2 ][Cd(AEAE)2 ]′[CdI4 ]2 (1 ), was prepared and characterized by spectroscopic methods and single-crystal X-ray diffraction. The reaction of AEAE with a 1:1 mixture of CdI2 and HgI2 was also investigated. The complex, [Cd(AEAE)2 ][I2 Hg( μ -I2 )2 HgI2 ] (2 ), was synthesized and characterized. Compounds1 and2 represent the first tridentate binding modes of an AEAE type ligand with Cd 2+ . Geometrical investigation for complexes containing Cd(N amine 2 O alcohol )2, CdIn, and HgIn environment were carried out using the CSD software. Also different possible diastereomers which can be formed in coordination of a pair of tridentate AEAE ligands in octahedral geometry were studied and discussed. Abstract :